Enhancing the Digital Classroom Experience through the Integration of Interactive Flat Panel and Tug of Knowledge as Cloud-Based Learning Media - Ayu Saputri Bahar; Iriandy (Information Technology Education Journal, 2025)
This study aims to develop and implement cloud-based learning media through the integration of the Interactive Flat Panel (IFP) and Tug of Knowledge in order to enhance the digital learning experience in the classroom. The study employed a Research and Development (R&D) design using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research participants comprised 32 students from the Family Welfare Education Study Program, Faculty of Engineering, Universitas Negeri Makassar. Data were collected through observations of student engagement, documentation of learning interactions, and analysis of task outcomes, which were subsequently analyzed using descriptive quantitative methods based on a 1–5 response scale. The results revealed an increase in student engagement, as indicated by an average engagement score of 4.35, as well as an improvement in group discussion participation of approximately 28% compared to learning conditions prior to the implementation of the media. In addition, 87.5% of students provided positive responses to the use of this media, particularly with regard to interactivity, collaboration, and learning motivation. These findings indicate that the integration of the Interactive Flat Panel and Tug of Knowledge as cloud-based learning media is effective in creating a more interactive, collaborative, and measurable digital learning experience and is aligned with the needs of 21st-century learning.